EVIDENCE FOR A WIDE RANGE OF ULTRAVIOLET OBSCURATION IN z similar to 2 DUSTY GALAXIES FROM THE GOODS-HERSCHEL SURVEY - Penner, K; Dickinson, M; Pope, A; Dey, A; Magnelli, B; Pannella, M; Altieri, B; Aussel, H; Buat, V; Bussmann, S; Charmandaris, V; Coia, D; et al. (2012)
Dusty galaxies at z ∼ 2 span a wide range of relative brightness between rest-frame mid-infrared (8 μm) and ultraviolet wavelengths. We attempt to determine the physical mechanism responsible for this diversity. Dust-obscured galaxies (DOGs), which have rest-frame mid-IR to UV flux density ratios ≳ 1000, might be abnormally bright in the mid-IR, perhaps due to prominent emission from active galactic nuclei and/or polycyclic aromatic hydrocarbons, or abnormally faint in the UV. We use far-infrared data from the GOODS-Herschel survey to show that most DOGs with 1012 L ⊙ ≲ LIR ≲ 1013 L ⊙ are not abnormally bright in the mid-IR when compared to other dusty galaxies with similar IR (8-1000 μm) luminosities. We observe a relation between the median IR to UV luminosity ratios and the median UV continuum power-law indices for these galaxies, and we find that only 24% have specific star formation rates that indicate the dominance of compact star-forming regions. This circumstantial evidence supports the idea that the UV- and IR-emitting regions in these galaxies are spatially coincident, which implies a connection between the abnormal UV faintness of DOGs and dust obscuration. We conclude that the range in rest-frame mid-IR to UV flux density ratios spanned by dusty galaxies at z ∼ 2 is due to differing amounts of UV obscuration. Of galaxies with these IR luminosities, DOGs are the most obscured. We attribute differences in UV obscuration to either (1) differences in the degree of alignment between the spatial distributions of dust and massive stars or (2) differences in the total dust content. © 2012 The American Astronomical Society. All rights reserved.